Análisis de la comunicación, liderazgo y cambio organizacional en el contexto de la industria automotriz - Delgado Leos, Alexis; VARGAS SALGADO, MARIA MARISELA (2020)
http://natal.uern.br/periodicos/index.php/RTEP/index